Dimes Square and Other Plays - Gasda, Matthew (Rowman & Littlefield Publishers, 2023)
Performed in loft apartments, pop-up theatres, and other nontraditional spaces, the 2022 underground hit Dimes Square announced Matthew Gasda as a dramatist of lasting power and impressive range, the theatrical chronicler of a self-chronicling generation. At a time when large, institutional theatres were still finding their post-pandemic footing, this brutal, hilarious portrait of New York City scenesters drew in new and diverse audiences by distilling the zeitgeist of our strange new era—a bitter cocktail of dirtbag politics, casual depravity, and pitiless ambition. Bringing together four of Gasda’s most penetrating works—Dimes Square, Quartet, Berlin Story, and Minotaur—this collection surveys a fractured and exhausted cultural-intellectual landscape. From squalid apartments to country estates to hipster bars, these plays give us characters grasping for meaning and human connection in an age of material abundance and moral dislocation. Unflinching, yet marked by exquisite moments of grace, they mark the arrival of a significant dramatic voice.